2020
DOI: 10.30886/estima.v18.844_in
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-level laser therapy on the healing of foot ulcers in people with diabetes mellitus

Abstract: Objective: Identify the effects of low-level laser therapy on the healing of diabetic foot. Method: Systematic review of the PubMed, LILACS, SciELO, CINAHL, Cochrane, Web of Science and Scopus databases, in which 92 articles were identified and six were included in the final sample after the eligibility criteria. Results: The articles pointed out as effects of laser therapy the effectiveness in the progression of the tissue repair process of the diabetic foot, pain relief, anti-inflammatory action, increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…9 However, it is pertinent to discuss the importance of health education with the patients during therapy, especially regarding glycemic control, foot care, use of appropriate shoes, and a healthy lifestyle to improve the success of PDT. 13 The current study contributes to improving the awareness of healthcare professionals regarding new protocols and medical therapies using adjuvant technologies with better cost-ben-…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…9 However, it is pertinent to discuss the importance of health education with the patients during therapy, especially regarding glycemic control, foot care, use of appropriate shoes, and a healthy lifestyle to improve the success of PDT. 13 The current study contributes to improving the awareness of healthcare professionals regarding new protocols and medical therapies using adjuvant technologies with better cost-ben-…”
Section: Discussionmentioning
confidence: 96%
“…Although there are favorable reports regarding the application of PDT, 11,12 newer investigations can provide additional evidence about the effectiveness of PDT in the treatment of DFU. 13 A study identified that health professionals, even those with qualifications to operate LASERs, have doubts regarding the dosage, wavelength, time, and number of applications to be used. 14 Therefore, it is important that health professionals, especially wound experts, understand the new approach of PDT in treating infected ulcers and incorporate it into their practice to promote optimized healing and reduce the number of complications due to DFU.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from osteomyelitis research, the effect of LLLT on bone repair was thoroughly carried out and showed stimulation of bone production;[ 30 31 32 ] therefore, the positive effect of this treatment modality can be postulated. A stimulating effect was recorded in terms of blood and lymph neovascularisation,[ 33 34 ] synthesis of RNA, DNA, collagen and its precursors, as well as positive effects on the levels of prostaglandin, phagocyte cytoplasmic granules, cell proliferation and production of adenosine-5’- triphosphate. [ 35 36 ] Furthermore, an existent penetration of LED 635-nm low-level light through the soft and hard tissues of the jaws was demonstrated[ 37 ] which implies that the complete jaw bone thickness receives therapeutic doses.…”
Section: Discussionmentioning
confidence: 99%
“…Its use is safe and valuable in wound treatment due to its wound-healing, anti-inflammatory, analgesic, and edema-reducing effects, reducing the recurrence rate of deep ulcers (5)(6) . In addition, a systematic review of the effects of LLLT on ulcers due to diabetic vasculopathy suggests that adjuvant therapy may improve neovascularization and minimize the risk of complications (7) . Light Amplification by Stimulated Emission of Radiation (LASER) uses electromagnetic radiation, which differs from normal light due to its specific physical properties.…”
Section: Introductionmentioning
confidence: 99%